Charlie et le grand ascenseur de verre - Dahl, Roald; Blake, Quentin (Paris : Gallimard Jeunesse, 1949)
Taking up where Charlie and the Chocolate Factory leaves off, Charlie, his family, and Mr. Wonka find themselves launched into space in the great glass elevator.
Keywords: Charlie and the Chocolate Factory -- Children's fiction